Dystonia induced by combined treatment with L-dopa and MK-801 in parkinsonian monkeys. - Rupniak, N; Boyce, S; Steventon, M; Iversen, S; Marsden, C (1992)
We examined whether the N-methyl-D-aspartate antagonist MK-801 (dizocilpine) would reverse parkinsonism or potentiate the effects of L-dopa in primates treated with 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). In contrast to its effect in rodent models, treatment with MK-801 (0.1 mg/kg) caused bradykinesia and ataxia in parkinsonian primates, but no locomotor stimulation. Coadministration of MK-801 (0.1 mg/kg) with L-dopa (20 mg/kg) induced marked dystonia accompanied by bradykinesia and ataxia. Dystonia was not induced by either treatment given alone. These findings indicate that MK-801 should not be advocated as an adjunct to dopamine agonist therapy in Parkinson's disease.